2012
DOI: 10.1111/j.1708-8208.2009.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

The Peri‐Implantitis: Implant Surfaces, Microstructure, and Physicochemical Aspects

Abstract: There are two ways of looking at secondary failures of osseointegration; one is to reflect on possible causes for the failure, the other focuses on the pathology per se. In the first case, background factors such as mechanical trauma (adverse loading) or inflammations/infections are being discussed as the cause of failure. Then peri-implantitis is a term reserved for implant disturbance due to inflammation/infections only. However, irrespective of the original reason for the failure being adverse loading or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
191
0
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(207 citation statements)
references
References 69 publications
(149 reference statements)
2
191
0
14
Order By: Relevance
“…Microbial infection is one of the main causes of implant failure [4,5]. During the process of surgery, implants are susceptible to bacterial contamination on skin and mucous membranes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Microbial infection is one of the main causes of implant failure [4,5]. During the process of surgery, implants are susceptible to bacterial contamination on skin and mucous membranes [6].…”
Section: Introductionmentioning
confidence: 99%
“…3 In this study implants were left undisturbed in titanium sterile airtight containers for 4 weeks to evaluate if passivation of the surface could mask the remnants of Al and Si. No changes were observed upon re-examination.…”
Section: Surface Chemistrymentioning
confidence: 99%
“…2011 Nov-Dec;25(6):492-9 inflammatory response. 3 Since the architecture of the gingival crevice surrounding implants is more fragile than the structure around natural teeth, using a cordless retraction paste for gingival retraction in implant dentistry appears to have considerable potential to afford a less traumatic procedure, compared to the other available techniques. 4 This in vitro study evaluated the effect of a cordless retraction paste material, Expasyl  (Acteon), on TiUnite  (Nobel Biocare) implant surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the formation of dental biofilm on the implant surface plays a role in the development of peri-implantitis [5]. The biofilm in peri-implantitis has a more complex microbial composition compared with periodontitis.…”
Section: Introductionmentioning
confidence: 99%